2010
DOI: 10.1016/j.fertnstert.2010.02.021
|View full text |Cite
|
Sign up to set email alerts
|

Will decreasing assisted reproduction technology costs improve utilization and outcomes among minority women?

Abstract: Objective To evaluate ART utilization and outcomes in minority women seeking care at enhanced access, military ART programs. Design Retrospective cohort Setting Federal ART programs Patients 2,050 women undergoing first cycle, fresh, non-donor ART from 2000–2005 Intervention None Main outcome measure(s ): ART utilization rate, clinical pregnancy rate, live birth rate Results African American (AA) women had an almost fourfold increased utilization of ART and Hispanic women had decreased utilization.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
32
0
2

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(36 citation statements)
references
References 21 publications
2
32
0
2
Order By: Relevance
“…This perception of overriding economic barriers resonates with findings among infertile US minorities (Inhorn et al 2009) and observed increases in the uptake of assisted reproductive services among African Americans when costs of care are reduced (Feinberg et al 442 G.A. Jae et al 2006, McCarthy-Keith et al 2010. Our study also highlights the ethnic diversity of families affected by SCD and demonstrates that access to IVF and PGD poses a socioeconomic concern regardless of ethnicity.…”
Section: Discussionsupporting
confidence: 85%
“…This perception of overriding economic barriers resonates with findings among infertile US minorities (Inhorn et al 2009) and observed increases in the uptake of assisted reproductive services among African Americans when costs of care are reduced (Feinberg et al 442 G.A. Jae et al 2006, McCarthy-Keith et al 2010. Our study also highlights the ethnic diversity of families affected by SCD and demonstrates that access to IVF and PGD poses a socioeconomic concern regardless of ethnicity.…”
Section: Discussionsupporting
confidence: 85%
“…Compared to minority women, white women have a higher incidence of male factor infertility (19,21,37,49).…”
Section: Infertility Diagnosismentioning
confidence: 99%
“…White women may be more likely to have PCOS, endometriosis, and/or other ovulation disorders compared with black or Hispanic women, and there is conflicting evidence on whether PCOS is more common in Asians than whites undergoing IVF (19,21,24,37,(49)(50)(51)(52). Though unlikely to fully explain disparities, ethnic differences in the prevalence and metabolic/reproductive consequences of PCOS have been previously identified (14).…”
Section: Infertility Diagnosismentioning
confidence: 99%
“…Yet studies have shown that utilization of assisted reproductive technology (ART) services by Hispanic women has not increased, even when economic barriers are minimized (5). In a study of military personnel, despite enhanced access to reproductive services, Hispanic patients did not use ART to the same extent as other ethnic groups (6). Other factors, such as social and cultural influences, may explain the significantly lower use of reproductive services compared with the white and African American populations (5).…”
mentioning
confidence: 99%